Continuity of Tradition in the Uzbek Puppet Theatre - Kadirova S.M (Genius Journals, 2024)
The article deals with a unique form of theatrical art - puppet theater. The author of the article examines the unique development, problems, and prospects of the national puppet theater based on today's realities.
Keywords: Doll; screen; director